Wanprestasi dalam Perjanjian Kesepakatan Bersama Menurut KUH Perdata (Studi Kasus Putusan Perkara Nomor 488/Pdt.G/2016/Pn.Jkt.Sel) - Oktaviani, Eva; Sudiarto, Bambang (ETHNOGRAPHY: Journal of Design, Social Sciences and Humanistic Studies, 2024)
The Problem of Default in the Collective Agreement in Case Decision Number 488/Pdt.G/2016/PN. Jkt.Sel. who was appointed due to a dispute over a Collective Agreement Agreement between the plaintiff and the defendant against an object of resale and purchase of land and buildings, in the APKB made before the South Jakarta Notary. The research method used is the normative juridical method, which is literature research with an approach that is carried out based on the main legal material related to the object of research. The research method used is the normative juridical method, which is literature research with an approach that is carried out based on the main legal material related to the object of research. Based on the results of the research, it was found that the legal act of default occurred in Case Decision Number 488/Pdt.G/2016/PN. Jkt.Sel in the Collective Agreement is where the defendant is not willing to sell the building to the plaintiff and even the defendant makes a unilateral requirement even though the obligation to sell to the Defendant is part of the collective agreement that has been stated in the Deed of Collective Agreement that was made, and the consequences of the law of default in the Collective Agreement Agreement in Case Decision Number 488/Pdt.G/2016/PN. Jkt.Sel is against the Defendant who is convicted of default and the Plaintiff has the right to buy back the land and buildings aquo in accordance with the Deed of Collective Settlement Agreement